Ruth Blau: A Life of Purpose and Paradox - Inbari, Motti (Women in Judaism)

(untitled) (Women in Judaism, Inc., 2023)
The chapter describes Madeleine Lucette Ferraille, who later changed her name to Ruth Ben David/Blau, during World War Two in France. When the war broke, Lucette was married to a handsome French soldier and gave him a son, but she wanted more out of life than was within easy reach—more, indeed, than the Vichy regime encouraged. By 1943, she was divorced, with a BA from the University of Toulouse. That year, she also helped a female Jewish refugee escape deportation and certain death. Recruited by the Resistance in early 1944, Lucette, who was beautiful as well as brilliant, made her way into the heart of the local Gestapo by becoming the mistress of a Waffen-SS officer, continuing to spy on the Nazi headquarters just a few months before D-Day.